Clinical and brain SPECT scan response to zolpidem in patients after brain damage - Nyakale, Nozipho E; Clauss, Ralf P; Nel, Wally; Sathekge, Mike (Arzneimittelforschung, 2010)
Previous reports document transient improvements after daily zolpidem (CAS 82626-48-0) in patients with brain damage. This multi-patient study evaluates the response to zolpidem in neurologically disabled patients, using 99m TcHMPAO brain SPECT scans and clinical rating scales.23 of 41 consecutive adult patients, at least 6 months after brain damage were identified as neurologically disabled patients by scoring less than 100/100 on the Barthel Index. Causes of their brain damage included stroke (n = 12), traumatic brain injury (n = 7), anaphylaxis (n = 2), drugs overdose (n = 1) and birth injury (n = 1). The selected 23 patients had a baseline 99m TcHMPAO brain SPECT scan before starting daily zolpidem therapy and a second within two weeks of therapy, performed 1 h after 10 mg oral zolpidem. Scans were designated as improved when at least two of three assessors detected improvement after zolpidem. The rest were designated non improved. After four months daily zolpidem therapy, patients were rated on the Tinetti Falls Efficacy Scale (TFES) before and after zolpidem. The TFES ratings were compared using a Wilcoxon non parametric signed rank test. Scan improvers were compared with non improvers, using a two sample t test with unequal variance.Mean overall improvement after zolpidem on TFES was 11.3%, from 73.4/100 to 62.1/100 (p = 0.0001). 10/23 (43%) patients improved on SPECT scan after zolpidem. Their mean TFES improvement was 19.4% (±16.75) compared with 5.08% (±5.17) in 13/23 non improvers (p = 0.0081).This prospective study adds further evidence to previous reports of zolpidem efficacy in patients with established brain damage.
Keywords: CAS 82626-48-0; Clinical rating scale; SPECT; Stroke; Traumatic brain injury; Zolpidem